PENGEMBANGAN BAHAN AJARMEMBACA HIKAYAT KELAS XI BAHASA - Prasetiawati, Rika (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
The purpose of this study were (1) to describe the process of the development of teaching materials read the saga of eleventh grade language, (2) describe the quality of teaching materials read the saga of eleventh grade Language developed, including (a) the validity, (b) practicality,(c)effectiveness. This research is the development (Research and Development) is a research method used to produce a particular product. Data collection instruments used include sheet validation (learning experts Indonesian, a language, learning experts Indonesian literature and expert graphics), about the competency test (in the form of multiple choice questions contained in teaching materials reading the saga developed), the issue of judicial review (in the form of about stuffing contained in teaching materials reading saga) and sheets of observations(observationsheetactivitiesofteachersandstudents).